2016
DOI: 10.32693/bomg.29.1.2014.60
|View full text |Cite
|
Sign up to set email alerts
|

Ostracoda From Subsurface Sediments of Karimata Strait as Indicator of Environmental Changes

Abstract: Karimata Strait is a part of Sunda Shelf connected South China Sea with Malacca Strait, Indian Ocean and Java Sea. This shelf was a large Sunda Land that has been detected by many evidences as records of various paleo-environments. The purpose of this study is to recognize the characteristic community of ostracoda related to the environmental history of this shelf. Three selected cores sediments represented east (A), middle (B) and west (C) parts of Karimata Strait were used for Ostracoda based on standard met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
0
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
1
0
0
3
Order By: Relevance
“…Taking into account, the present geographical position and bathimetry (more than 30 m deep) of the core site, shallow neritic environment should have occupied the site since the early deposition of the core ca 1,800 yr B.P. The presence of shallow marine benthic foraminifers (Dewi, 2014) supports this argument, and proves that mangroves have been away from the core site when the core was firstly deposited. This study shows fifteen genera of benthic foraminifers identified in samples were taken from Zone 1.…”
Section: Pollen Assemblages and Environmental Changessupporting
confidence: 52%
“…Taking into account, the present geographical position and bathimetry (more than 30 m deep) of the core site, shallow neritic environment should have occupied the site since the early deposition of the core ca 1,800 yr B.P. The presence of shallow marine benthic foraminifers (Dewi, 2014) supports this argument, and proves that mangroves have been away from the core site when the core was firstly deposited. This study shows fifteen genera of benthic foraminifers identified in samples were taken from Zone 1.…”
Section: Pollen Assemblages and Environmental Changessupporting
confidence: 52%
“…Selain kedua spesies tersebut, beberapa genus yang hadir cukup melimpah di sebagian besar sampel adalah genus Foveoleberis, Pistocythereis, Pylectonophora, Cytherella, Loxoconcha dan Cytherelloidea. Penelitian Dewi (1993Dewi ( & 2000 di perairan utara Laut Jawa dan perairan selatan Kalimantan Selatan mengungkapkan bahwa kehadiran genusgenus tersebut mengindikasikan distribusi ostracoda masih berada dalam satu wilayah persebaran yang sama. Kehadiran genus-genus tersebut cukup umum di perairan Laut Jawa hingga bagian selatan Pulau Kalimantan.…”
Section: Hasil Dan Pembahasanunclassified
“…Kehadiran genus-genus tersebut cukup umum di perairan Laut Jawa hingga bagian selatan Pulau Kalimantan. Beberapa spesies dari genus tersebut, di antaranya spesies Foveoleberis cypraeoides, bahkan menjadi spesies endemik perairan wilayah Indo-Malaysia yang juga ditemukan melimpah di sekitar perairan Selat Malaka dan Singapura (Dewi, 2000).…”
Section: Hasil Dan Pembahasanunclassified
“…Respon mikrofauna tersebut tidak terbatas pada kelimpahan dan cangkang abnormal namun juga dapat dilihat dari kandungan kimia dan perubahan warna cangkang. Dewi (2014) Hasil pengolahan data berdasarkan Hammer dkk.,(2001) ditampilkan pada Tabel 2. Jumlah taksa antara 1 (BL16-001) dan 26 (BL16-10).…”
Section: Pendahuluanunclassified